2015
DOI: 10.18388/abp.2015_1092
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of caffeine against plant pathogenic bacteria

Abstract: The objective of the present study was to evaluate the antibacterial properties of a plant secondary metabolite - caffeine. Caffeine is present in over 100 plant species. Antibacterial activity of caffeine was examined against the following plant-pathogenic bacteria: Ralstonia solanacearum (Rsol), Clavibacter michiganesis subsp. sepedonicus (Cms), Dickeya solani (Dsol), Pectobacterium atrosepticum (Pba), Pectobacterium carotovorum subsp. carotovorum (Pcc), Pseudomonas syringae pv. tomato (Pst), and Xanthomonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 21 publications
2
31
0
1
Order By: Relevance
“…N-OH-Pip Is Not Bactericidal. To rule out that N-OH-Pip is toxic to bacterial growth in planta, we performed a minimum inhibitory concentration (MIC) assay (33) to measure potential bactericidal activity. Cultures of Psm ES4326, Pst DC3000, and Pst avrRpt2 (13,21,22).…”
Section: N-oh-pip Treatment Of Arabidopsis Leaves Is Sufficient To Inmentioning
confidence: 99%
“…N-OH-Pip Is Not Bactericidal. To rule out that N-OH-Pip is toxic to bacterial growth in planta, we performed a minimum inhibitory concentration (MIC) assay (33) to measure potential bactericidal activity. Cultures of Psm ES4326, Pst DC3000, and Pst avrRpt2 (13,21,22).…”
Section: N-oh-pip Treatment Of Arabidopsis Leaves Is Sufficient To Inmentioning
confidence: 99%
“…MIC assays were performed according to (Sledz, 2015) with slight modification. A single colony of Psm ES4326 or Pst DC3000 was incubated in LB broth, while a single colony of Pst avrRpt2 was incubated in NYGA broth without antibiotics and shaken (220 rpm) at 28°C for 24 hr.…”
Section: Minimum Inhibitory Concentration (Mic) Assaymentioning
confidence: 99%
“…glycinea was correlated with the increasing concentration of this compound [11]. Subsequently, Sledz et al [12] evaluated antibacterial activity of caffeine toward broad spectrum of plant pathogenic bacteria causing economic losses in crop and ornamental plant production worldwide: Clavibacter michiganensis subsp. sepedonicus (Cms), Dickeya solani (Dsol), Pectobacterium atrosepticum (Pba), Pectobacterium carotovorum subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine inhibited growth of the above-listed phytopathogens in broth cultures, increased their generation time, triggered morphological abbreviations, and finally exhibited bactericidal effect in concentrations from 40 to 100 mM [12]. Moreover, application of this compound reduced disease symptoms caused by Dsol on potato slices, whole potato tubers, and chicory leaves [12]. In addition, it was shown that the plant pathogenic bacterium tested could not develop any resistance to the caffeine treatment [12].…”
Section: Introductionmentioning
confidence: 99%